Textural, rheological and sensorial properties of mayonnaise fortified with Asian sea bass bio‐calcium. (17th October 2022) - Wijayanti, Ima; Prodpran, Thummanoon; Sookchoo, Pornsatit; Nirmal, Nilesh; Zhang, Bin; Balange, Amjad; Benjakul, Soottawat
Abstract: Asian sea bass bio‐calcium (ASBC) can be fortified in low calcium food product such as mayonnaise. To ensure the smoothness of fortified products, the particle size and fishy compounds of ASBC must be reduced. Ultrasonicated ASBC (U‐ASBC) was applied for different times (5–15 min) in the presence of hexane. ASBC and U‐ASBC had mean particle size (D43 ) of 21.87 ± 19.54 and 7.83 ± 7.10 μm, respectively. U‐ASBC had lowered volatile compounds. Mayonnaise fortified with ASBC had the augmented firmness, consistency and cohesiveness with increasing ASBC levels (0%–10%) ( p < 0.05). ASBC raised lightness ( L* ) and total color difference (Δ E *), but decreased a* and b*‐ values of mayonnaise in a dose dependent manner ( p < 0.05). Higher G ′, G ″, viscosity and shear stress value were observed in mayonnaise sample added with ASBC. However, lower acceptability was attained when mayonnaise was added with ASBC at level higher than 2.5% due to fishy odor and grittiness perceived by panelists. The lower droplet size with higher zeta potential of mayonnaise added with ASBC or U‐ASBC was related with the lower creaming index. Mayonnaise added with 7.5% U‐ASBC (M‐UBC‐7.5) had higher viscosity with lower creaming and thermal creaming index ( p < 0.05) than control and that containing 2.5% ASBC (M‐BC‐2.5). Denser and smaller droplet sizes were observed for M‐BC‐2.5 and M‐UBC‐7.5 than control. Lowest moisture, fat and carbohydrate contents were attained for M‐UBC‐7.5 with the higher protein, ash and calcium content ( p < 0.05). Fortification of mayonnaise with ASBC at 2.5% or U‐ASBC at 7.5% increased calcium content by 54 or 174 times, respectively, without sensorial changes.